Silanol-Assisted Aldol Condensation on Aminated Silica: Understanding the Arrangement of Functional Groups - Lauwaert, Jeroen; De Canck, Els; Esquivel, Dolores; Thybaut, Joris W.; Van Der Voort, Pascal; Marin, Guy B. (ChemCatChem, 2014)
Free silanol groups are known to promote the activity of aminated silica. In this work the effect of the silanol‐to‐amine ratio on the aldol condensation of 4‐nitrobenzaldehyde and acetone is investigated in a range from 0 to 2.4. Irrespective of the amine density, identical, moderate turnover frequencies are obtained if the silica exclusively has amines on its surface. The turnover frequency increases with increasing silanol‐to‐amine ratio until an upper limit is reached at a silanol‐to‐amine ratio of 1.7. At this upper limit the turnover frequency is a factor 5 higher than the turnover frequencies obtained with the monofunctional amine‐based catalysts. This increase is ascribed to hydrogen‐bridge interactions between the silanols and the carbonyl moiety of the reactants that provoke a more easy interaction between the carbonyl moiety and the amine as required for the aldol condensation. The observation that higher values than one for the silanol‐to‐amine ratio are required is rationalized by computer simulations. It was found that amine groups were grafted on the silica surface in a clustered manner, originating from positive deviations from ideality in the synthesis mixture, that is, from clustering of the amine precursor in the liquid phase. Let's troop together: The enhancing effect of free silanol groups on amine‐catalyzed aldol condensations is studied in great detail. It is concluded that at high amine loadings the amine functions tend to cluster on the catalyst surface.